aRt&D: Research and development in art - Brouwer, Joke; Fauconnier, Sandra; Mulder, Arjen; Nigten, Anne (Rotterdam V2_Publishing, 2005)
aRt&D: Research and Development in Art lays open a new investigative field of art that emerged in the last few decades as a result of media and technology influences. aRt&D introduces the diversity of this new art domain to a broader audience. It is the first book that is entirely dedicated to artistic research and development.In the past decades a new international trend has emerged within the arts, usually referred to as "electronic," "digital," or "interactive" art. In the 1980s, artists mainly worked with radio and video, where in the last fifteen years digital media and network technologies have emerged as their instruments of choice. This new art domain is characterized by collaboration between artists, designers, engineers and scientists, who join forces in researching and experimenting with new opportunities for using technology for artistic ends.aRt&D: Research and Development in Art not only provides a unique insight in the art practice through essays in which artists write about their personal experiences, it also develops a theoretical framework for these projects. The book contains contributions by the award-winning performance group Blast Theory, media artist Thecla Schiphorst, art critics Josephine Bosma and Rudolf Frieling, media theorist Andy Cameron, curators Mark Hansen and Inke Arns, philosopher Andrew Benjamin, and many others. Timothy Druckrey, expert in this field, evaluates the importance of artistic research and development so far. aRt&D positions itself as a pioneering work: it is the first book ever published that focuses in depth on interdisciplinary research and development from an artistic perspective. EssaysIntroductionAndrew Benjamin: Plurality of Actions: Notes on an Ontology of TechniqueJosephine Bosma: Net Art: Building Something out of NothingAndy Cameron: Dinner with Myron or: Rereading Artificial Reality 2: Reflections on Interface and ArtTimothy Druckrey: (Ad)Venture Aesthetics?Rudolf Frieling: Database and Context: Artistic Strategies within a Dynamic Field of ActionMark B.N. Hansen: Embodyment: The Machinic and the HumanAnne Nigten: Blurred Disciplines, Expressive Software Artist ProjectsArchined, Stealth and V2_LabArs Electronica Futurelab and BrucknerhausBlast TheorySara DiamondSher DoruffEdwin van der Heide and Lars SpuybroekMargarete Jahrmann and Max MoswitzerKnowbotic ResearchDavid LinkEsther PolakDavid RokebyQ.S. Serafijn and Lars SpuybroekChrista Sommerer and Laurent MignoneauZoltán Szegedy-Maszák and Márton FernezelyiTime's UpwhisperDocument